The Role of Parents in Improving Al-Quran Memorization at SDIT Adzikra Bogor - Khaidir Fadil; Qisti Hanifa; Suhendra (STKIP Al Islam Tunas Bangsa dan HEPI, 2024)
Education begins in the family environment, which consists of parents and children. Parents play a crucial role in influencing a child's development. Every parent certainly desires their children to be righteous and hopes that they will become Quran memorizers. This study aims to examine the role of parents in enhancing students' Quran memorization in the tahfidz program at SDIT Adzikra Bogor. Memorizing the Quran is an important activity that requires support from various parties, especially parents. This research employs a qualitative approach, utilizing data collection techniques through interviews, observations, and documentation. The findings indicate that parental involvement significantly impacts the development of children's memorization. Parents who actively provide motivation, guidance, and create a conducive environment can enhance their children's enthusiasm and concentration in memorizing the Quran. Conversely, parents who are less attentive tend to cause children to lose focus and enthusiasm for learning. This study concludes that active parental involvement in children's education, especially in the tahfidz program, is essential to achieving the desired learning outcomes.